Cost and Value of Routine Histopathologic Analysis after Adenoidectomy and Tonsillectomy - Hackenberg,Berit (2020)
Abstract Introduction Tonsillectomy and adenoidectomy are common procedures. Most surgeries in children and young adults are recommended due to recurring infections or obstructive constraints. However, occult malignant findings are reported in the literature. The clinical guidelines still refrain from recommending routine histopathologic analyses when discussing these procedures. Objective The present study aims to define the value of a routine histopathologic analysis after tonsillectomy, adenoidectomy and tonsillotomy. Methods We conducted a prospective survey including all German ear, nose and throat (ENT) departments, asking physicians about their current clinical practice and opinion. Furthermore, we reviewed all patients attending our department for tonsillectomy/adenoidectomy/tonsillotomy or a combination of these procedures between 2011 and 2016. In addition to this, a cost analysis was conducted to assess the financial burden of a routine histopathologic analysis. Results Most German ENT departments perform a routine histopathologic analysis after tonsillectomy/adenoidectomy/tonsillotomy. Despite this, only a minority deemed this approach necessary. Our retrospective review of the histopathologic analysis after tonsillectomy/adenoidectomy/tonsillotomy in our department rendered a cohort size of 2,157 patients. Within this group, there were no occult malignant findings. We found a yearly burden of 2,509,401€ for routine histopathologic analyses in patients under the age of 15 years in Germany in 2016. Conclusion We found a divergence between the physicians opinions and their current clinical practice concerning the question of whether to conduct routine histopathologic analyses. Even though there was no occult malignant finding in our cohort, unsuspected malignant findings are reported in the literature. Therefore, we call for a discussion on clinical practice guidelines.